Property Law in Namibia - Samuel K. Amoo (Pretoria University Law Press (PULP), 2014)
About the publication Property Law in Namibia provides an autochthonous discussion of property law in Namibia. It does not only capture the constitutional, statutory and common law sources of property law in Namibia, but it also covers currently topical subjects such as property rights of women and land reform in Namibia. The publication is meant to be utilised by law academics, property law lecturers, legal practitioners and conveyancers, law students, students pursuing specialised land related programmes such as land use planning and officials in government ministries. Property Law in Namibia contains chapters on traditional concepts of property law such as the scope and nature of the law of property, classifications of things, real rights and personal rights, ownership and possession. Chapter 9 is devoted entirely to remedies, which is a departure from the norm, but where relevant, appropriate remedies are indicated in the specific parts of the text. In order to give prominence to Namibian property jurisprudence topics on the genesis of the land tenure systems of Namibia, land reform, and property rights of women in Namibia have either been dealt with in separate chapters or been included as parts of other chapters. This publication is meant to be utilised by law academics, property law lecturers, legal practitioners and conveyancers, law students, students pursuing specialised land related programmes such as land use planning and officials About the editor: Samuel K. Amoo is Advocate of the High Court for Zambia and Attorney of the High Court of Namibia. Associate Professor of Law (University of Namibia). Acting Director, Justice Training Centre (JTC) Property Law in Namibia by Samuel K. Amoo 2014 ISBN: 978-1-920538-22-4 Pages: 247 Print version: Available Electronic version: Free PDF available